Impacts of online intermediary's platform openness under asymmetric quality information. (May 2023) - Tong, Yang; Li, Lixu; Yang, Danqin; Jiang, Xia
Highlights: The implications of platform openness in the context of a better-informed manufacturer is studied. Information sharing may narrow the region of the win–win outcome. Online intermediary cannot always induce the manufacturer to share quality information through platform openness. Platform openness may decrease the value of information sharing for the online intermediary. Abstract: In a platform economy, alongside the traditional reselling channel, online intermediaries (e.g., Amazon and JD.com ) open their platforms to allow manufacturers to distribute products directly to consumers via an agency channel, i.e., platform openness. This paper investigates the implications of platform openness when a manufacturer possesses product quality information unknown to the online intermediary. We analyze a signaling game between a manufacturer and an online intermediary, in which the better-informed manufacturer first sets the wholesale price, which it may use to signal private quality information. Based on the wholesale price, the intermediary decides what quantity of the product to sell through the reselling channel. Finally, if the intermediary opens its platform, the manufacturer decides what quantity of the product to sell through the agency channel. We find that the effects of platform openness on the manufacturer and the online intermediary depend on three model parameters: the commission rate, the degree of channel substitution, and the degree of quality differentiation. Interestingly, information sharing may narrow the region of the win–win outcome in which platform openness benefits both intermediary and manufacturer, which differs from the situation in which the online intermediary is better informed than the manufacturer. Moreover, the online intermediary cannot always induce the manufacturer to share quality information through platform openness; similarly, platform openness may even decrease the value of information sharing for the online intermediary.